Funds of Identity and Humanizing Research as a Means of Combating Deficit Perspectives of Homelessness in the Middle Grades - Matthew Moulton (MDPI AG, 2018)
Youth experiencing homelessness have seldom had the opportunity to contribute to conversations about policies and practices that impact their day-to-day lives. Brinegar highlighted middle level education research’s contribution to the lack of representation of the voices of youth from marginalized perspectives. Where opportunities lack, dominant narratives persist. The word homeless often conjures deficit-laden images of ineptitude and unintelligence. This qualitative humanizing research study worked with one participant, AJ, who created maps and other identity artifacts as a means of illuminating his funds of identity that were then analyzed using Creswell and Poth’s data analysis spiral. Though results showed AJ to be a young adolescent with multiple funds of identity, the purpose of this article is to present how AJ draws great strength and purpose from his identity as a creator, despite transience between schools, who leverages technology for his personal and academic benefit. These results describe a young adolescent whose resilience and funds of identity transcend dominant narratives surrounding homelessness and point to opportunities for educator support in curriculum development and school-level policy.